1998
DOI: 10.21273/hortsci.33.4.655
|View full text |Cite
|
Sign up to set email alerts
|

Potato Yield and Quality Response to Deficit Irrigation

Abstract: Four potato (Solanum tuberosum L.) varieties were grown under four season-long sprinkler irrigation treatments in three successive years (1992-94) on silt loam soil in eastern Oregon. The check treatment was irrigated when soil water potential (SWP) at the 0.2-m depth reached -60 J·kg-1 and received at most the accumulated evapotranspiration (Etc) to avoid exceeding the water-holding capacity of the top 0.3 m of soil. The three defici… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
52
1
1

Year Published

2001
2001
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 78 publications
(56 citation statements)
references
References 0 publications
2
52
1
1
Order By: Relevance
“…There were The relatively low tuber yields obtained in the farmer's and I40 irrigation treatments compared to those in I100 were associated with lower tuber number m À2 and tuber weight (Table III). In previous studies, Cappaert et al (1992) and Shock et al (1992) stated that adequate water supply before and during tuber initiation increased the number of tubers per plant, whereas after tuber initiation it increased tuber weight (Stark and McCann, 1992;Shock et al, 1998). Therefore, water stress should be avoided during tuber initiation and development which are the most critical periods sensitive to water stress.…”
Section: Crop Yieldmentioning
confidence: 96%
“…There were The relatively low tuber yields obtained in the farmer's and I40 irrigation treatments compared to those in I100 were associated with lower tuber number m À2 and tuber weight (Table III). In previous studies, Cappaert et al (1992) and Shock et al (1992) stated that adequate water supply before and during tuber initiation increased the number of tubers per plant, whereas after tuber initiation it increased tuber weight (Stark and McCann, 1992;Shock et al, 1998). Therefore, water stress should be avoided during tuber initiation and development which are the most critical periods sensitive to water stress.…”
Section: Crop Yieldmentioning
confidence: 96%
“…Several of the parameters in the model depend on the soil, including , m, s and p c . Potatoes are frequently grown in silt loam soil (Shock et al, 1998). Therefore, we chose to use the parameter values for the 'Silt Loam G.E.3' soil from van Genuchten (1980) (i.e.…”
Section: Geometric Soil Environmental Plant and Solute Parameter Vmentioning
confidence: 99%
“…Previous studies have shown that adequate water supply before and during tubers initiation increases the number of tubers per plant [15] [16]; whereas, after tubers initiation, it increases their individual sizes [17] [18]. Water deficit produces smaller tuber size and lower yields [7] [8].…”
Section: Introductionmentioning
confidence: 99%